Des paiements pour services environnementaux en faveur des populations locales ? Regards de l’administration forestière sur le mécanisme de compensations pour mise en défens marocain - Sarah Vanuxem (VertigO, 2016)
The Morrocan authorities have adopted a system of payments for ecological services (PES) as a mechanism for awarding subsidies for deferred grazing areas (SDGA). This move could have allowed the local population to exert greater control over its own territory, and even to rediscover its own bio-cultural heritage. Any hope for a genuine retake by the local population has however been in vain, since the main operating purpose of the system was really to strengthen the power of the Forest Department. A study of the Morrocan pilot project REDD (Reducing Emissions from Deforestation and Degradation) confirms this analysis. This system is to be added to the SDGA mechanism in the Mâamora forest, with the local population mostly left out of the decision-making process.